Examining the influence of brand recognition on the intention to repurchase halal store brand products: a review - Isa, Maryam Ladi; Kamarulzaman, Nitty Hirawaty; Hashim, Haslinda; Abdul Halim Lim, Sarina (Human Resource Management Academic Research Society, 2024)
In recent years, the halal market has experienced substantial growth, becoming increasingly significant in the global economy. The market, initially associated with food and beverages for Muslim consumers, has expanded its scope to encompass various industries, including pharmaceuticals, cosmetics, finance, fashion, and travel. The objective of this review was to examine how brand awareness influences consumer behavior and loyalty in the halal store brand. Our findings reveal that factors such as religious observance, ethical and moral values, quality assurance, cultural identity, and the expanding global market contribute to the growing demand for these products. Consumers seek halal store brands not only for religious reasons but also because they align with their ethical considerations and provide assurance of quality and safety. Furthermore, these brands play a role in preserving cultural identity, especially in regions with minority Muslim populations. The relationship between brand awareness and repurchase intention has been explored in multiple empirical studies, highlighting a consistent positive association. Higher brand awareness leads to increased repurchase intention across different industries and product categories. Effective communication strategies, emotional connections, and positive associations with halal brands have been identified as key drivers of this relationship. To enhance brand awareness and foster brand loyalty among halal store brands, marketers can employ various strategies, including leveraging digital and social media platforms, partnering with influencers, prominently displaying halal certifications, creating informative and educational content, engaging with the local community, and collaborating with other halal-certified businesses. To stand out in a competitive halal market, brands should emphasize distinct values, innovation, personalization, ethics, and transparency. Addressing challenges and seizing opportunities helps establish brand awareness and drive consumer loyalty.